Who's afraid of Virginia Woolf? [videorecording (DVD)] - Nichols, Mike; Taylor, Elizabeth, 1932-2011; Burton, Richard, 1925-1984; Segal, George; Dennis, Sandy, 1937-1992; Albee, Edward, 1928-2016 (Warner Home Video, 2006)
A couple is invited to the home of a professor and his sharp-tongued wife, and are treated to verbal battles by their hosts.